Negative capacitance of ZnGa2Se4/Si nano-heterojunction diode - Yahia, I. S.; Sakr, G. B.; Shenouda, S. S.; Fadel, M.; Fouad, S. S.; Yakuphanoğlu, Fahrettin (Springer Heidelberg, 2013)
The negative capacitance (NC) behavior in p-ZnGa2Se4/n-Si nano-crystalline HJD was characterized by admittance-voltage method. The C-V, G-V and R (s) -V for the studied diode were analysed in the frequency range of 1-5 MHz and in the temperature range of 303-423 K. The capacitance and conductance plots were interpreted in terms of interface states and series resistance. The C-V and G/omega-V plots exhibit a pounced peak due to the interface states and the series resistance effects. The negative capacitance behavior in the studied diode can be explained in terms of the transient currents.
Keywords: Nonlinear-Optical Properties; Light-Emitting-Diodes; Impedance Spectroscopy; Electrical-Properties; Series Resistance; Schottky Diodes; Thin-Films; C-V; Frequency; Interface